Dampak The Great Lockdown dengan Strategi Colaborative Funding Cooperation Terhadap Imunitas Bisnis UMKM - Muhammad Milzam; Danang Satrio; Choliq Sabana (Jurnal Ekonomi Dan Bisnis, 2021)
This study aims to determine the economic impact felt by MSMEs due to the Covid 19 pandemic as well as to find solutions to help economic recovery in MSMEs, especially in Pekalongan City. Based on the data and facts in the field that we get with direct data collection techniques (questionnaires), the appropriate research methodology for processing these data and facts includes statistical analysis and descriptive analysis. The results of the data processing indicate that MSMEs in the city of Pekalongan experienced a decline in turnover of 53.5% during the study period. And based on an open question, most MSMEs need additional capital to sustain their business. And most of the MSMEs of Pekalongan City are of the opinion that access to business capital from savings and loan cooperatives is easier than Banks. Based on the results of statistical data processing, with the best practice method, it can be concluded that the government needs to adopt the concept of Equity Crowdfunding to restore the condition of MSMEs. This concept needs to be adjusted to the level of financial literacy of MSMEs which tend to choose savings and loan cooperatives to access business capital